Periodontal disease and cancer risk: A nationwide population-based cohort study - Kim, Eun Hwa; Nam, Sunghyun; Park, Chung Hyun; Kim, Yitak; Lee, Myeongjee; Ahn, Joong Bae; Shin, Sang Joon; Park, Yu Rang; Jung, Hoi In; Kim, Baek-Il; Jung, Inkyung; Kim, Han Sang (Frontiers in Oncology, 2022)
Background: Although emerging evidence suggests that periodontitis might increase the risk of cancer, comorbidity and lifestyle behaviors, such as smoking and body mass index (BMI), may have confounded this reported association. This study aimed to investigate whether chronic periodontitis is associated with cancer risk using a large, nationwide database. Methods: We conducted a population-based, retrospective cohort study using data from the Korean National Health Insurance Cohort Database obtained between January 2003 and December 2015. We included 713,201 individuals without a history of cancer who were followed up to 10 years. Confounding factors included demographic factors (age, sex, income, and residential area), lifestyle behaviors (smoking history and BMI), and comorbidities, such as hypertension, diabetes, heart failure, and pulmonary disease, using the Charlson Comorbidity Index. Multivariable Cox regression analysis was applied to estimate the adjusted hazard ratio (aHR) for cancer risk. Results: Of the 713,201 participants, 53,075 had periodontitis and were placed in the periodontitis group; the remaining 660,126 individuals were included as the control group. Overall, the cumulative incidence of cancer in the periodontitis group was 2.2 times higher than that in the control group. The periodontitis group had an increased risk of total cancer compared to the control group after adjusting for age, sex, comorbidities, BMI, and smoking history (aHR, 1.129; 95% confidence interval [CI], 1.089-1.171; P<0.0001). When examining specific cancer types, significant associations were also observed between periodontitis and stomach cancer (aHR, 1.136; 95% CI, 1.042-1.239; P=0.0037), colon cancer (aHR, 1.129; 95% CI, 1.029-1.239; P=0.0105), lung cancer (aHR, 1.127; 95% CI, 1.008-1.260; P=0.0353), bladder cancer (aHR, 1.307; 95% CI, 1.071-1.595; P=0.0085), thyroid cancer (aHR, 1.191; 95% CI, 1.085-1.308; P=0.0002), and leukemia (aHR, 1.394; 95% CI, 1.039-1.872; P=0.0270). There was no significant association between the development of secondary malignancy and periodontitis in cancer survivors who were alive 5 years after they were diagnosed with the primary malignancy. Conclusions: Periodontal disease, including periodontitis, was associated with increased risk of cancer, which persisted after controlling for confounding factors. Further prospective research is warranted to establish a causal relationship.